The role of NGO workplace policies in eliminating HIV/AIDS in South Africa : an analysis of two case studies - Robinson-Davis, Suzanne (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.